سياسة الحكم التركي - المصري التعليمية في السودان )1821 - 1885م( - د. أسامة عبد الله محمد الأمين (White Nile Journal for Studies and Research, 2018)
The study dealt with t policy Turkish-Egyptian Educational rule in Sudan (1821/1885). The aim of the study was to clarify the Educational policy which planed by Turkish rulers in Sudan. The study adopted the historical descriptive analytical method. It concluded with several results, the most important of which were the tendency of the Turkish rulers to help Islamic institutions financially Religious Education from Taxation, the expansion of modern Education in Sudan has been linked to provide of Sudanese elements that can occupy some government jobs.